ChemInform Abstract: An Efficient Copper‐Catalyzed One‐Pot Synthesis of 1‐Aryl‐1, 2, 3‐triazoles from Arylboronic Acids in Water under Mild Conditions. Issue 12 (March 2016) - Hao, Changbo; Zhou, Changjian; Xie, Jianwei; Zhang, Jie; Liu, Ping; Dai, Bin
Abstract: The procedure involves an one‐pot two‐step 1, 3‐dipolar cycloaddition reaction of various aryl boronic acids, sodium azide followed with terminal alkynes under environmentally friendly reaction conditions.